The Effects of Co-prescription of Pantoprazole on the Clozapine Metabolism - Kuzin, Maxim; Schoretsanitis, Georgios; Haen, Ekkehard; Dammann, Gerhard; Hiemke, Christoph; Gründer, Gerhard; Paulzen, Michael (Pharmacopsychiatry, 2020)
Background Polypharmacy including somatic medications such as proton pump inhibitors is a common phenomenon in psychiatric care. The aim of this study was to evaluate the pantoprazole effects on clozapine metabolism.Methods A large therapeutic drug-monitoring database containing plasma concentrations of CLZ was analyzed. The results were stratified into four groups: a non-smoking (n=250) and a smoking group (n=326), and two groups co-medicated with pantoprazole: non-smokers (n=26) and smokers (n=29). The analysis was based on the non-parametrical Mann-Whitney U test (M-W-U) with a significance level of 0.05.Results Differences reached statistical significance for pharmacokinetic parameters between CLZ monotherapy and co-medication with pantoprazole neither in smokers nor in non-smokers (p>0.05 for M-W-U in pairwise comparisons). In patients with clozapine monotherapy, smokers had a higher daily dosage of CLZ compared to non-smokers (mean dosage 363±181 vs. 291±145 mg/day, p<0.001 for M-W-U).Conclusions Adding pantoprazole to an ongoing treatment with clozapine does not alter the metabolism of clozapine to a significant extent.
Keywords: therapeutic drug monitoring; clozapine; pantoprazole; CYP2C19; smokers